Kemampuan Siswa Dalam Menyelesaikan Soal-Soal OPENENDED - Shasmitha, Shasmitha; Rusdy A.Siroj, Rusdy A.Siroj; Amrina Rizta, Amrina Rizta (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2019)
This study aims to determine the ability of students to solve open-ended questions on the subject of integer summation in class IV SD Negeri Plaju District. The method used in this study is descriptive qualitative. The population in the study was 798 students consisting of all fourth grade students of SD Negeri Plaju District. Data were collected from the results of giving a written test consisting of 4 questions consisting of the sum of two numbers that have 3 types of questions and the sum of three numbers that have 7 types of questions. After analyzing the data, students' ability to solve the open-ended sum of two numbers given guiding questions is categorized very well with a percentage of 81.01%. The ability of students to solve the open-ended problem of the sum of three numbers given a guiding problem that is known to be two numbers in the previous row is categorized enough with the percentage of 42.6%. The ability of students to solve open-ended questions on the sum of three numbers known to one number by determining both numbers is categorized as less by the percentage of 25.83%. The ability of students to solve open-ended questions on the sum of three numbers given a guiding problem which is known to be one number in the previous row is categorized as less by the percentage of 33.3%. The ability of students to solve open-ended questions on the sum of three numbers not given a guiding question is categorized as less by the percentage of 20.54%.